Karakterisasi Ekson 4 Gen DRD4 pada Ayam Arab Tiara G15 dengan Tingkah Laku Feather Pecking - Achmad Farajallah; Pristina Tuti Wijayanti; Achmad Alfiyan; Maria Ulfah (Jurnal Ilmu Pertanian Indonesia, 2024)
Feather pecking (FP) is a potentially fatal behavioral disorder in chickens. Various factors, including genetics such as DRD4 gene, affected this behavior. The Arab TIARA G15 chicken is a laying hen breed selected based on FP behavior. However, genetic selection linked to this FP as not yet been conducted. This study aimed to characterize the 4th exon of the DRD4 gene in Arab golden red TIARA G15 chickens and confirm its potential as an FP genetic marker. The study used 30 TIARA G15 chickens that were divided into three groups: high feather pecking (HFP) (n = 10), low feather pecking (LFP) (n = 10), and control (n = 10). The DNA extraction kit extracted total genomic DNA from each blood sample. The 4th exon of the DRD4 gene was amplified using primer pairs MU140-141. Amplicons from samples within a group were pooled in a single tube and sequenced using the Sanger method. The sequencing results were analyzed for nucleotide variation using MEGA6 software. Nucleotide sequences obtained from each group were 642 bp, consisting of partial intron 3 (55 bp), full-length exon 4 (202 bp), and partial 3'UTR (385 bp). None of the three groups of Arab golden red TIARA G15 chickens were found to have any nucleotide variants in the partial intron 3, full-length exon 4, and 3'UTR regions of the DRD4 gene. Consequently, selecting the full-length exon 4 of the DRD4 gene for FP behavior was not feasible. Keywords: arab chicken, DRD4, feather pecking, golden red